Internet Memes as a Current Phenomenon of Political Internet Communication in Germany: Grand Coalition Thematic Group - L. N. Rebrina (Научный диалог, 2022)
The object of the research is Internet memes that constitute the thematic group “Grand Coalition” and appeared during the reign of the parliament of the Federal Republic of Germany 2018–2021. Internet memes selected under the given denotative and temporal features are analyzed in dynamics within N. A. Zinoviev’s typology, based on a set of dichotomies (“truth — lie”, “character — event”, “tradition — innovation”, “background — figure”, “image — text”, “thought — action”). A conclusion is made about the field organization of the Internet meme structure. This structure includes the remaining constant kernel formed by the visual template and the generalized meaning of the Internet meme. It is shown that the specificity of the functioning of the precedent phenomenon as part of Internet memes lies in its transformation through the distribution or replacement of elements and subsequent reinterpretation. The very development of the Internet meme, its successful promotion online supposes the decontextualization of the primary meme and its further recontextualization in new communicative situations. The precedent phenomena involved are most often the conductors of negative meanings. The following signs of the grand coalition are regularly reflected in Internet memes — incapacity, mistrust on the part of citizens, and a bad reputation of its members.